MENINGKATKAN HASIL BELAJAR SISWA DENGAN MELALUI MEDIA VISUAL PADA PEMBELAJARAN TEMATIK (TEMA 1 SUB TEMA 2) DI KELAS I SD NEGERI 04 KAJAI PARIAMAN - Pindawati Pindawati (Ensiklopedia Education Review, 2020)
The low student learning outcomes in Thematic Learning Theme 1, Sub Theme 2 are caused by several factors, including student activities that are lacking in media that does not exist and the lack of source books for students so that it affects the student's involvement in the learning carried out. In this case the researcher as a class conducted a research entitled "Improving Student Learning Outcomes by Using Visual Media in Thematic Learning (Theme 1 Sub Theme 2) in class I SD Negeri 04 Kaja Pariaman" with the formulation of the problem, namely "Can Visual Media Improve the results? Student Learning in Thematic Learning (Theme 1 Sub Theme 2) in Class I SD Negeri 04 Kaja "The purpose of this study is to improve student learning outcomes in learning theme 1 sub theme 2 in class I SD Negeri 04 Kaja." This research was conducted at SD Negeri 04 Kaja in grade I, and was implemented in two cycles. The first cycle consists of two meetings, the second cycle is also held twice. The problems that will be discussed when using this visual media are determined by the teacher as a researcher. After the first cycle using visual media, the results obtained were only at the beginning, namely active students only reached 60%. At the end of the second cycle, there was a significant increase, student learning activities on thematic (Theme 1 Sub Theme 2) and learning outcomes. This can be seen in the ongoing learning and the results of the initial and final tests whose average score is 63 to 88, increases. Thus the use of visual media is very supportive and good in improving student learning outcomes in Thematic learning (Theme 1 Sub Theme 2).